Research Development of Energy Efficient Water Hydraulics Manipulator for Underwater Application - Yusof, Ahmad Anas; Wasbari, Faizil; Ibrahim, Mohd Qadafie (Trans Tech Publications, 2013)
The paper presents research development of water hydraulics manipulator test rig for underwater application at Center for Advance Energy Research, Faculty of Mechanical Engineering, Universiti Teknikal Malaysia Melaka. The test rig is designed in order to study the effectiveness of using water hydraulics system for underwater manipulation application. With objective to promote sustainability and energy saving, the manipulator system is targeted for usage in an underwater scenario, possibly on a small submarine or underwater remotely operated vehicle (ROV). Underwater vehicles normally utilize the use of oil hydraulics for propulsion, manipulation and instrument control. The research on underwater manipulator that uses the surrounding sea water itself as the power and energy carrier for control is now possible with the current development in water hydraulics technology.